Sistem Informasi Koperasi Simpan Pinjam Komunitas Koperasi Bhumi Karya - Faisal Fajar Ramadhan; Dewi Rosmala; Fauzan Irzani; Firman Aldiansyah; MH Tazul; Renddy Nurcahya (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Abstract Bhumi Karya Cooperative is an organization focused on the savings and loan activities of its members. Loans with low interest rates and various types of savings are offered to enhance the welfare of the members. However, challenges in the effectiveness of transaction data management, the conventional handling of savings and loan applications, and financial reports managed using Microsoft Excel are faced by the cooperative. The development of a web-based information system is deemed essential, as this system not only allows members to conduct transactions remotely, such as the previously manual savings and loan applications, but also accelerates the processes of member data entry, transaction recording, report generation, and service provision to members anywhere. Additionally, prospective members can register online, thereby increasing the overall operational efficiency of the cooperative